Pelatihan praktik melukis teknik fresco bagi siswa Kelas X di Sekolah Menengah Atas Negeri 14 Makassar - Muh. Saleh Husain; Andi Nur Maida; Benny Subiantoro (Universitas Negeri Makassar, 2019)
The material of the learning process of the theory of fine arts education and the practicum of fine arts education, whose behavior to directed at the process of serving the concepts of aesthetic concepts, creativity and work, adjusted to the level of ability of the students themselves. The connection in this case, to avoid the passivity of students during the learning process of art education, through the presentation of educational media implemented by the teacher will be a motivation for creative thinking to apply freedom to express their feelings and realize real work increating works of art in accordance with the assignment of structured subject matter from the teacher. The tendency to words increasing teaching in fine arts education will benefit from being presented informal academic instituions that are applied in Makassar public High School 14, regarding the learning process in an innovative direction, both in the form of basic theoretical offerings and the practice of creating fine art is pretty much marked through a form of teaching process that gives room for creativity, explanation, learning to work on Fresco techniques, which of course begins with the practice of learning to draw sketches that are applied to Makassar14 Senior High School students, so students will experience a change from not knowing to being know, through growth in attitudes and growth in thinking more creative and intelligent.